Enabling partnering in the Malaysian construction industry: A research on policies for effective implementation - Abdul Nifa, Faizatul Akmar; Radzuan, Kamaruddin; Mohd Nawi, Mohd Nasrun; Abdul Rahim, Syukran (Asian Research Publishing Network (ARPN), 2016)
In response to the issues faced by the Malaysian construction industry, the Construction Industry Development Board (CIDB) has identified and recommended partnering as a method to overcome the current problems within the industry.This is also in line with the establishment of “Public Private Partnership Unit” (3PU) under the Prime Minister’s Department in 2009 to oversee the implementation of partnering in the Malaysian construction industry. It is crucial that the policies in place should facilitate the practitioners so that the full potential of partnering to overcome the many problems in the Malaysian construction industry can be fully utilized. This paper describes the conceptual aspects and the preliminary stage of an ongoing research. The research aims to identify whether current policies in place are serving as an enabler for effective partnering or a deterrent to the adoption of partnering by the practitioners in the Malaysian construction industry. It is determined that apart from issues identified from literature review, the preliminary qualitative study has revealed that enabling factors such as political and legal system influence towards partnering should be considered in formulating effective policies for successful partnering in the Malaysian construction industry.